Diagnosis and treatment of congestive heart failure secondary to dilated cardiomyopathy in a hedgehog. (23rd December 2013) - Delk, K. W.; Eshar, D.; Garcia, E.; Harkin, K.
<x xml:space="preserve">Abstract</x> A one‐year‐old African pygmy hedgehog (Atelerix albiventris) was evaluated for severe respiratory distress. Physical examination findings included marked dyspnoea, cyanosis and tachypnoea. Radiographic findings included an enlarged heart and pulmonary oedema, and dilated cardiomyopathy was confirmed via echocardiogram. The patient was treated for congestive heart failure because of dilated cardiomyopathy with furosemide, enalapril, pimobendan and l‐carnitine. Within 24 hours of treatment, the pulmonary oedema and cyanosis had resolved. Following discharge, clinical improvement was noted by the owner and echocardiogram confirmed improved fractional shortening. Cardiomyopathy has been reported at post‐mortem examination in hedgehogs, but there are no reports of ante‐mortem diagnosis and treatment. Performing baseline cardiac assessment in hedgehogs is recommended, and treatment with l‐carnitine and pimobendan may improve outcome, as carnitine deficiency is a possible cause of cardiomyopathy in hedgehogs. Successful emergency treatment of congestive heart failure in the hedgehog of this report may be effective for other hedgehogs presented with similar clinical signs.